Time decay for solutions to the Stokes equations with drift - Schonbek, M; Seregin, G (World Scientific Publishing, 2017)
In this note, we study the behavior of Lebesgue norms ||v(·, t)||pof solutions v to the Cauchy problem for the Stokes system with drift u, which is supposed to be a divergence free smooth vector-valued function satisfying a scale invariant condition.